IDENTIFIKASI FAKTOR YANG MEMPENGARUHI KINERJA KEPALA SEKOLAH - Bintang, Salman (TABULARASA, 2013)
The purpose of this paper was to determine the indicators that affect the performance of the principal. Efforts to improve the performance of these principals can be done in various ways. One of them is to do a theoretical study of the factors that allegedly associated with these performance factors. Theoretically the factors that affect the performance factors are very numerous and complex. Performance variables studied by analyzing various factors that can influence it. Assessment and analysis of the relationship between variables is discussed to measure the effect of one variable to another variable. These variables are: (1) motivation, (2) organizational commitment, (3) authority, and (4) performance. In this paper discussed how to influence motivation, authority, organizational commitment to the performance of the principal.